1997
DOI: 10.1002/maco.19970480804
|View full text |Cite
|
Sign up to set email alerts
|

High temperature corrosion behaviour of a new Ni‐30Fe‐10Al‐Cr‐Alloy

Abstract: Dedicated to Dr. U. Heubner on the occasion of his 65th birthdayThe high temperature corrosion behaviour of a new duplex nickel-base alloy containing about 30 mass% iron, 10 mass% aluminium and 8 mass% chromium was determined in both air and hot process gases containing methanekydrogen, sulphur dioxide and hydrogen sulphide, respectively. It was found that the corrosion resistance against carburisation, sulphidation and oxidation was excellent due to the formation of a dense, protective alumina scale. The adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…During creep testing the DS alloy showed high microstructural stability, i. e. only slight coarsening was observed [117]. These results are in accordance with results for a DS eutectic A1 + B2 Fe -Al -Ni alloy, which also showed increased creep resistance that was proportional to the reciprocal lamellae spacings [143,144].…”
Section: Directional Solidificationsupporting
confidence: 88%
“…During creep testing the DS alloy showed high microstructural stability, i. e. only slight coarsening was observed [117]. These results are in accordance with results for a DS eutectic A1 + B2 Fe -Al -Ni alloy, which also showed increased creep resistance that was proportional to the reciprocal lamellae spacings [143,144].…”
Section: Directional Solidificationsupporting
confidence: 88%
“…Therefore the addition of chromium to Fe 3 Al resulted in a change in the nature of the protective oxide coating [12]. It has also been observed that Cr additions accelerated the formation of a continuous Al 2 O 3 scale in Ni-30Fe-10Al-Cr alloy [21]. XPS analysis by Velon et al [22] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 showed that the oxide on Cr-containing Fe 3 Al consisted of a continuous layer of (Al, Cr) 2 It is worth noting that Zamanzade et al [13] showed that for Fe 3 Al, the presence of hydrogen decreased the shear modulus, the energy for dislocation nucleation and the dislocation mobility.…”
Section: Resultsmentioning
confidence: 99%